Caracterización de la incidencia y severidad de trips (Frankliniella tuberosi) y gusano blanco (Premnotrypes vorax) en el rendimiento de semilla certificada de papa (Solanum tuberosum) - Nájera Lumbi, Edison Efraín (2025)
The objectives of the research were: To characterize the incidence and severity of thrips and white grub on the yield of certified potato seed. To evaluate the level of incidence of thrips and white grub in potato crops. To determine the severity of thrips and white grub damage in potato crops. To establish the yield of certified seed in potato crops. Regarding the objectives of the strata, they demonstrated satisfactory characteristics in relation to the characterization of the incidence and severity of thrips and white grub. The potato crop faces various problems in the agroecological zones of the Bolívar province, mainly related to adverse conditions, soil fertility degradation, poor agricultural practices, and low use of quality and/or certified seed. The presence of thrips and white grub can lead to a productivity reduction of up to 80%, which is why it is essential to establish parameters for incidence and severity. The research considered strata composed of different potato varieties. As a result, in the three strata, using Tukey tests, Fisher’s test, and simple linear correlation and regression analysis, it was found that the plant height averaged 71.4 in E1, the highest number of tubers per plant was in E3 with 42 tubers, the tuber weight per plant was 2.45 kg/plant in E3, with a white grub incidence of 2.41 and a severity of 2 in E3, resulting in a crop yield of 2492.8. As for thrips, no statistical data were obtained because no symptoms related to the pest were observed, which justifies the application of profenos. In this way, significant contributions were made due to the good agronomic and productive management of the potato crop.